Hydrothermal carbonization of biomass residuals: a comparative review of the chemistry, processes and applications of wet and dry pyrolysis. Issue 1 (January 2011) - Libra, Judy A; Ro, Kyoung S; Kammann, Claudia; Funke, Axel; Berge, Nicole D; Neubauer, York; Titirici, Maria-Magdalena; Fühner, Christoph; Bens, Oliver; Kern, Jürgen; Emmerich, Karl-Heinz
The carbonization of biomass residuals to char has strong potential to become an environmentally sound conversion process for the production of a wide variety of products. In addition to its traditional use for the production of charcoal and other energy vectors, pyrolysis can produce products for environmental, catalytic, electronic and agricultural applications. As an alternative to dry pyrolysis, the wet pyrolysis process, also known as hydrothermal carbonization, opens up the field of potential feedstocks for char production to a range of nontraditional renewable and plentiful wet agricultural residues and municipal wastes. Its chemistry offers huge potential to influence product characteristics on demand, and produce designer carbon materials. Future uses of these hydrochars may range from innovative materials to soil amelioration, nutrient conservation via intelligent waste stream management and the increase of carbon stock in degraded soils.